2016
DOI: 10.3390/met6060137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidation Temperature on the Oxidation Process of Silicon-Containing Steel

Abstract: Abstract:The oxidation behavior of silicon-containing steel was studied by applying segmented heating routes similar to the atmosphere and heating process in an industrial reheating furnace. The oxidation tests were carried out on a simultaneous thermal analyzer at heating temperatures of 1150˝C-1300˝C. The morphologies of Fe 2 SiO 4 were observed by SEM, and the penetration depths of the Fe 2 SiO 4 layer at different oxidation temperatures were determined by using the Image-Pro Plus 6.0 software. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Figure 2 shows the SEM images of the oxide scale in the two tested steels obtained with the backscattered electron (BSE) detector. As depicted in previous studies [15,16], the oxide scale mainly consists of three different layers, i.e., the upper layer Fe2O3, middle layer FeO + Fe3O4, and inner layer FeO/Fe2SiO4. The outer layers of Fe2O3 and FeO + Fe3O4 are brittle and easy to wipe off, but the inner layer of FeO/Fe2SiO4 strongly adheres to the metal matrix and is retained completely.…”
Section: In Situ Observation Of the Melting Process Of Fe2sio4mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the SEM images of the oxide scale in the two tested steels obtained with the backscattered electron (BSE) detector. As depicted in previous studies [15,16], the oxide scale mainly consists of three different layers, i.e., the upper layer Fe2O3, middle layer FeO + Fe3O4, and inner layer FeO/Fe2SiO4. The outer layers of Fe2O3 and FeO + Fe3O4 are brittle and easy to wipe off, but the inner layer of FeO/Fe2SiO4 strongly adheres to the metal matrix and is retained completely.…”
Section: In Situ Observation Of the Melting Process Of Fe2sio4mentioning
confidence: 99%
“…Figure 2 shows the SEM images of the oxide scale in the two tested steels obtained with the backscattered electron (BSE) detector. As depicted in previous studies [15,16], the oxide scale mainly consists of three different layers, i.e., the upper layer to obtain the areas of Fe 2 SiO 4 in unit widths, the total areas are divided by the width of the measured images [11]. The red area represents the distributions of solid Fe 2 SiO 4 and the measured area can represent the amount of Fe 2 SiO 4 .…”
Section: In Situ Observation Of the Melting Process Of Fe 2 Siomentioning
confidence: 99%
“…Previous studies have confirmed that the iron scale in this steel contains Fe 2 O 3 , Fe 3 O 4 , FeO, and Fe 2 SiO 4 [11,14,15]. The intimal scale consists of Fe 2 SiO 4 and FeO.…”
Section: Sem Observationsmentioning
confidence: 67%
“…Mouayd et al [12] and Suarez et al [13] found that the amount and penetrative depth of Fe 2 SiO 4 -FeO increases with the Si content. In addition, He et al [14] reported that the morphology of Fe 2 SiO 4 4 -FeO and provides a theoretical reference toward preventing red scale defect in Si-containing steels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation